Kamenev-Type Oscillation Criteria of Second-Order Nonlinear Dynamic Equations on Time Scales - Yang-Cong Qiu; Qi-Ru Wang (Discrete Dynamics in Nature and Society)
Using functions from some function classes and a generalized Riccati technique, we establish Kamenev-type oscillation criteria for second-order nonlinear dynamic equations on time scales of the form (p(t)ψ(x(t))k∘xΔ(t))Δ+f(t,x(σ(t)))=0. Two examples are included to show the significance of the results.